2021
DOI: 10.3390/act10100248
|View full text |Cite
|
Sign up to set email alerts
|

Axial Motion Characterization of a Helical Ionic Polymer Metal Composite Actuator and Its Application in 3-DOF Micro-Parallel Platforms

Abstract: In this work, a helical ionic polymer metal composite (IPMC) was fabricated by thermal treatment in a mold with helix grooves. The axial actuation behaviors of the helical IPMC actuator were observed, and the electromechanical and electrochemical characteristics were evaluated. The experimental results showed that as the voltage increased and the frequency decreased, the axial displacement, axial force, and electric current of the actuator all increased. Compared with square wave and sinusoidal signals, the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The simulation using the model provided was in good agreement with the experimental results of simple harmonic input motion. Wu et al [ 14 ] designed a spiral IPMC, built a multiphysics model, and simulated the model using Comsol Multiphysics. The simulation data of the model is in good agreement with the data measured by the prepared spiral IPMC sample.…”
Section: Physical‐based Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…The simulation using the model provided was in good agreement with the experimental results of simple harmonic input motion. Wu et al [ 14 ] designed a spiral IPMC, built a multiphysics model, and simulated the model using Comsol Multiphysics. The simulation data of the model is in good agreement with the data measured by the prepared spiral IPMC sample.…”
Section: Physical‐based Modelsmentioning
confidence: 99%
“…Cheong et al [ 148 ] and Chang et al [ 18 ] both proposed wirelessly powered IPMC operating devices based on external radio frequency (RF) magnetic field operation. Using the developed axially actuating IPMCs, Wu et al [ 14 ] developed a three‐degree of freedom microparallel platform (Figure 11g), which can realize complex coupled motion of pitch, roll, and yaw.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, researchers found that the performance of IPMC is associated with its specifc capacitance and conductivity. Wu et al measured the electrochemical properties of helical IPMC and found that its properties were closely related to mechanical properties [15]. Sun [16] analyzed an IPMC MWCNT/MnO 2 composite electrode, and proved that the IPMC's capacitor, the output power density, specifc capacitance, and the changing trend of strain are basically identical; they also found that the performance of IPMC is related to the content of MWCNT and MnO 2 .…”
Section: Introductionmentioning
confidence: 99%